Novel bi-allelic MSH4 variants causes meiotic arrest and non-obstructive azoospermia - Peng Li; Zhiyong Ji; Erlei Zhi; Yuxiang Zhang; Sha Han; Liangyu Zhao; Ruhui Tian; Huixing Chen; Yuhua Huang; Jing Zhang; Huirong Chen; Fujun Zhao; et al. (BMC, 2022)
Abstract Background Non-obstructive azoospermia (NOA) is one of the most severe type in male infertility, and the genetic causes of NOA with meiotic arrest remain elusive. Methods Four Chinese families with NOA participated in the study. We performed whole-exome sequencing (WES) for the four NOA-affected patients in four pedigrees. The candidate causative gene was further verified by Sanger sequencing. Hematoxylin and eosin staining (H&E) and immunohistochemistry (IHC) were carried out to evaluate the stage of spermatogenesis arrested in the patients with NOA. Results We identified two novel homozygous frameshift mutations of MSH4 and two novel compound heterozygous variants in MSH4 in four pedigrees with NOA. Homozygous loss of function (LoF) variants in MSH4 was identified in the NOA-affected patient (P9359) in a consanguineous Chinese family (NM_002440.4: c.805_812del: p.V269Qfs*15) and one patient with NOA (P21504) in another Chinese family (NM_002440.4: c.2220_2223del:p.K741Rfs*2). Also, compound heterozygous variants in MSH4 were identified in two NOA-affected siblings (P9517 and P9517B) (NM_002440.4: c.G1950A: p.W650X and c.2179delG: p.D727Mfs*11), and the patient with NOA (P9540) (NM_002440.4: c.G244A: p.G82S and c.670delT: p.L224Cfs*3). Histological analysis demonstrated lack of spermatozoa in seminiferous tubules of all patients and IHC showed the spermatogenesis arrested at the meiotic prophase I stage. Consistent with the autosomal recessive mode of inheritance, all of these mutations were inherited from heterozygous parental carriers. Conclusions We identified that six novel mutations in MSH4 responsible for meiotic arrest and NOA. And these results provide researchers with a new insight to understand the genetic etiology of NOA and to identify new loci for genetic counselling of NOA.